x^2 = the first integer
(x - 1)^2 = the second integer.
x^2 - (x - 1)^2 = ?
First, let's plug a number into our equation for x.
(2)^2 - (2 - 1)^2 = ?
4 - (1)^2 = ?
4 - 1 = 3
As we can see the difference is odd but it's also the sum of the two consecutive integers.
2 + 1 = 3.
This works for all numbers. Let's plug another number into our equation for x.
(4)^2 - (4 - 1)^2 = ?
16 - (3)^2 = ?
16 - 9 = 7
4 + 3 = 7
Try any number and it will always be odd.
Answer:
I'm not really sure what you're asking because there's no image.
Step-by-step explanation:
please try to reword it and maybe show a picture .
The answer is 6. Please mark BRAINLIEST!! :D
Answer:
Height of cylinder (h) = (4/3)R
Step-by-step explanation:
Given:
Radius of cylinder (r1) = R
Height of cylinder (h) = H
Radius of sphere (r2) = R
Volume of cylinder = volume of sphere
Find:
Height of cylinder (h) = H = ?
Computation:

Height of cylinder (h) = (4/3)R
X=31, the other post justifies, I just wanted to make it more accessible for if someone just needs the answer :)